Uptake of a patient‐centred dynamic choice model for HIV prevention in rural Kenya and Uganda: SEARCH SAPPHIRE study - Jane Kabami; Elijah Kakande; Gabriel Chamie; Laura B. Balzer; Maya L. Petersen; Carol S. Camlin; Marilyn Nyabuti; Catherine A. Koss; Elizabeth A. Bukusi; Moses R. Kamya; Diane V. Havlir; James Ayieko (Journal of the International AIDS Society, 2023)
Abstract Introduction Person‐centred HIV prevention delivery models that offer structured choices in product, testing and visit location may increase coverage. However, data are lacking on the actual uptake of choices among persons at risk of HIV in southern Africa. In an ongoing randomized study (SEARCH; NCT04810650) in rural East Africa, we evaluated the uptake of choices made when offered in a person‐centred, dynamic choice model for HIV prevention. Methods Using the PRECEDE framework, we developed a persont‐centred, Dynamic Choice HIV Prevention (DCP) intervention for persons at risk of HIV in three settings in rural Kenya and Uganda: antenatal clinic (ANC), outpatient department (OPD) and in the community. Components include: provider training on product choice (predisposing); flexibility and responsiveness to client desires and choices (pre‐exposure prophylaxis [PrEP]/post‐exposure prophylaxis [PEP], clinic vs. off‐site visits and self‐ or clinician‐based HIV testing) (enabling); and client and staff feedback (reinforcing). All clients received a structured assessment of barriers with personalized plans to address them, mobile phone access to clinicians (24 hours/7 days/week) and integrated reproductive health services. In this interim analysis, we describe the uptake of choices of product, location and testing during the first 24 weeks of follow‐up (April 2021−March 2022). Results A total of 612 (203 ANC, 197 OPD and 212 community) participants were randomized to the person‐centred DCP intervention. We delivered the DCP intervention in all three settings with diverse populations: ANC: 39% pregnant; median age: 24 years; OPD: 39% male, median age 27 years; and community: 42% male, median age: 29 years. Baseline choice of PrEP was highest in ANC (98%) vs. OPD (84%) and community (40%); whereas the proportion of adults selecting PEP was higher in the community (46%) vs. OPD (8%) and ANC (1%). Personal preference for off‐site visits increased over time (65% at week 24 vs. 35% at baseline). Interest in alternative HIV testing modalities grew over time (38% baseline self‐testing vs. 58% at week 24). Conclusions A person‐centred model incorporating structured choice in biomedical prevention and care delivery options in settings with demographically diverse groups, in rural Kenya and Uganda, was responsive to varying personal preferences over time in HIV prevention programmes.